Об исторической топографии городище Картал - Бруяко, И.В. (Материалы по археологии Северного Причерноморья, 2009)
The hillfort "Kartal" is the multilevel archaeological site of Eneolithic-Middle Ages period. It is situated on the left bank of Lower Danube nearby from the modem village Orlovka (Reni district, Odessa region). In this article are analyzed topographical changes in site's area, which have been connected with practical activities of ancient population at different historical times. It is established that site was unfortified in the period of Gumelnitza culture. It occupied high part (acropolis - "Stone Hill") and small teritory joined to it (suburb). The inhabltants of the next period- Chemavoda culture (Late Eneolithic)- built the defensive ditch, which has divided the site into two parts - acropolis and suburb - for the first time. In the 4th century В.С. the populations of Getian culture built defensive bank, just over the ditch of Chemavoda period. At last, the teпain has acquired modem view (XIX - first halfXXcent.) in the Roman period. 1t happened after the Roman fort, which defended approach to the crossing of Danube, had been erected here.